2020
DOI: 10.1093/braincomms/fcaa050
|View full text |Cite
|
Sign up to set email alerts
|

Expanded neuromuscular morbidity in Hodgkin lymphoma after radiotherapy

Abstract: Our study aims to quantitate neuromuscular morbidity from radiotherapy in Hodgkin lymphoma including: (i) frequency and (ii) time of onsets for neurological localizations; (iii) degree of disabilities and (iv) number of clinical visits compared to cardiopulmonary Hodgkin lymphoma-radiation complications. Medical records from Mayo Health systems were retrieved; identifying neuromuscular radiation treated Hodgkin lymphoma-complications from 1 January 1994 to 31 December 2016. Of an estimated 4100 post-radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Although a myopathic process on its own is not expected to give rise to myokymic discharges, the radiation treatment presumably led to both a peripheral nerve irritability giving rise to myokymic discharges, as well as a superimposed radiation-induced myopathy within the field of radiation. [9][10][11] The conspicuous absence of myokymic discharges in hand muscles among radiation-associated cases is also noteworthy. It is unknown whether this difference was because the innervating axons happened to be spared from the field of radiation in these cases because of the greater anatomical distance from the field of radiation (as most radiation beams are directed at axial structures), or due to some intrinsic resilience to hyperexcitability of these muscles after radiation damage to their innervating nerves.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although a myopathic process on its own is not expected to give rise to myokymic discharges, the radiation treatment presumably led to both a peripheral nerve irritability giving rise to myokymic discharges, as well as a superimposed radiation-induced myopathy within the field of radiation. [9][10][11] The conspicuous absence of myokymic discharges in hand muscles among radiation-associated cases is also noteworthy. It is unknown whether this difference was because the innervating axons happened to be spared from the field of radiation in these cases because of the greater anatomical distance from the field of radiation (as most radiation beams are directed at axial structures), or due to some intrinsic resilience to hyperexcitability of these muscles after radiation damage to their innervating nerves.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, two patients in the postradiation group were noted to have myopathic motor unit potentials on EMG, and in both instances the electromyographer commented on probable underlying radiation‐induced myopathy. Although a myopathic process on its own is not expected to give rise to myokymic discharges, the radiation treatment presumably led to both a peripheral nerve irritability giving rise to myokymic discharges, as well as a superimposed radiation‐induced myopathy within the field of radiation 9‐11 …”
Section: Discussionmentioning
confidence: 99%
“…2 A recent review of the lifetime risk of neuromuscular complications in 4,100 radiation-treated cases with Hodgkin lymphoma identified that approximately 1 of 20 patients had neurologic radiation-induced complications including neuropathy, plexopathy, myopathy, and myelopathy. 3 Radiation-induced brachial 4,5 and lumbosacral plexopathies 6 occur in diverse cancer types. The symptom onset for radiation-induced neuropathies is typically delayed occurring on average 20 years postradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The symptom onset for radiationinduced neuropathies is typically delayed occurring on average 20 years postradiation. 3,7 Chronic progressive weakness is typical, without neuropathic pain or sensory symptoms, and no cure is currently available. [3][4][5][6][7][8][9] The pathogenic mechanism behind chronic postradiation neurologic complications is believed to relate to microvascular injury from the radiation exposure leading to fibrosis in both neural and non-neural tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation